2019
DOI: 10.15252/embr.201948073
|View full text |Cite
|
Sign up to set email alerts
|

HOPS/TMUB1 retains p53 in the cytoplasm and sustains p53‐dependent mitochondrial apoptosis

Abstract: Apoptotic signalling by p53 occurs at both transcriptional and nontranscriptional levels, as p53 may act as a direct apoptogenic stimulus via activation of the intrinsic mitochondrial pathway. HOPS is a highly conserved, ubiquitously expressed shuttling protein with an ubiquitin-like domain. We generated Hops À/À mice and observed that they are viable with no apparent phenotypic defects. However, when treated with chemotherapeutic agents, Hops À/À mice display a significant reduction in apoptosis, suggesting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 63 publications
(145 reference statements)
6
38
0
Order By: Relevance
“…HOPS has been shown to interact with the tumor suppressors p19 Arf enabling its stabilization through the involvement of the nucleolar protein nucleophosmin (NPM) 14 . Recently, HOPS has been reported to be a fundamental regulator of mitochondrial p53 activity during DNA damage-induced apoptosis 15 . HOPS is abundantly expressed in the brain, where it plays a role in the regulation of basal synaptic transmission 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…HOPS has been shown to interact with the tumor suppressors p19 Arf enabling its stabilization through the involvement of the nucleolar protein nucleophosmin (NPM) 14 . Recently, HOPS has been reported to be a fundamental regulator of mitochondrial p53 activity during DNA damage-induced apoptosis 15 . HOPS is abundantly expressed in the brain, where it plays a role in the regulation of basal synaptic transmission 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…We can speculate that HOPS localisation in nucleus and the differentiation of lens cells are accompanied by a progressive arrest of proliferation, which triggers the differentiation. Recently, we demonstrated that HOPS UBL plays a notable role, as protein modifier, regulating p53 stability and triggering the p53-mediated apoptosis [ 5 ]. In such a complex structure as lens is the role of protein modifiers and ubiquitin is fundamental and the machinery involved in proteasomal pathway execution is strategic in the shift from proliferation to differentiation [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…HOPS is involved in p53 stabilisation, p53-mediated mitochondrial apoptosis and p53 nuclear import. This evidence suggests that HOPS acts as potential tumour suppressor by its ubiquitin-like domain [ 5–7 ].…”
Section: Introductionmentioning
confidence: 99%
“…( A ) Phylogeny of ubiquitin (Ub), ubiquitin-like proteins (UBLs) and Ub/UBL domains fused to human proteins. Genome stability associations are highlighted in green and apply to the following in addition to ISG15: Ub [ 3 , 10 ], Parkin [ 47 , 48 , 49 , 50 ], NEDD8 [ 11 ], UBTD1 [ 51 ], FAT10 [ 12 ], SF3A1 [ 52 ], RAD23A and RAD23B [ 53 ], TMUB1 (aka HOPS) [ 54 , 55 , 56 ], UBL5 (aka HUB1) [ 12 ], UHRF1 [ 57 , 58 , 59 ], ELOB (aka TCEB2) [ 60 ], USP48 [ 61 , 62 ], ATG12 [ 63 ], BAG6 [ 64 ], RBCK1 [ 65 ], BAG1 [ 66 , 67 ], HERPUD1 [ 68 ], UFM1 [ 12 ], UBQLN4 [ 69 ], SUMO1, SUMO2 and SUMO3 [ 70 ]; sequence similarity to ubiquitin is highlighted in the outermost ring ranging from GABARAP (9.59%) in red over a white midpoint to NEDD8 (58%) in blue. Ub/UBL domains are limited to curated UniProt entries.…”
Section: Isg15 and Isgylationmentioning
confidence: 99%